'Sono solo parole': Facing challenges entailed in developing and applying terminologies to document nursing care. (26th February 2022) - Malabusini, Cecilia
Abstract: Nurses' need to document activities is urgent. The panorama of available terminologies is heterogeneous. It seems necessary to understand the premises of available tools and their limits and benefits to make conscious choices and shape future development. Taxonomies (e.g., North American Nursing Diagnosis Association) and 'pure terminologies' (e.g., International Classification for Nursing Practice), or nursing languages, are available tools to document nurses' activities and to produce theoretical models or reference systems. These tools respond first to a practical problem: 'translating' nursing facts into linguistic descriptions. Taxonomies make reality describable through exhaustive definitions designed inductively. Thus, I argue that their philosophical basis is naïve semantics. Their framework is a closed hierarchy, that is, a system that provides defined levels of concepts, structured through dichotomous rules. This causes the problem of determining boundaries between concepts, and thus between phenomena, which I call the problem of 'closing the concept enclosure'. Rigid metaphysical structures are unable to cope with the complexity of phenomena that nurses deal with, so they seem to be unable to describe them. I follow Wittgenstein's argument, from Philosophical Investigations, which is useful to understand this challenge: the definition of terms is not a problem of lack of suitable words or an agreed decision, but is achieved by training in practice. Pure terminologies give us another way to address the question. They are usually composed of a glossary of terms, paired with rules to combine them to manage meaning. They are more like natural language and this implies adapting more to phenomena. Then, I argue that their philosophical background is a pragmatic approach to language, and I discuss some consequences and objections. Finally, I find that the development of pure terminologies rather than taxonomies in documenting nursing activities allows us to achieve key objectives, such as improving nursing visibility and measurability in health records, without jeopardising person‐centred care.